Effectiveness Analysis of CCTV and Announcer on Accident Prevention In Construction OHS Culture - Alfadin Azzahrawaani El Nauval; Agung Wahyudi Biantoro (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of Real-Time CCTV System, Announcer, Safety Leadership Program 4.0, and the work environment on Occupational Health and Safety (OHS) culture, as well as their impact on accident prevention in construction projects. The research adopts a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. Data were collected through questionnaires distributed to respondents at construction sites and analyzed to test the validity, reliability, and relationships among variables in the structural model. The results indicate that the Safety Leadership Program 4.0 and the work environment have a significant influence on the development of an OHS culture. Meanwhile, the Real-Time CCTV System showed a near-significant influence, and the Announcer had no significant impact on OHS culture. Regarding accident prevention, the Real-Time CCTV System and Announcer demonstrated a direct and significant effect, while OHS culture, Safety Leadership Program 4.0, and the work environment did not show a significant direct influence. These findings suggest that technological approaches are more effective in providing immediate responses to potential hazards, whereas cultural development and leadership require more time and integrated strategies. In conclusion, this study highlights the importance of integrating technology, safety leadership, and a supportive work environment to build a strong OHS culture and sustainably reduce the risk of workplace accidents in construction projects.